Caracterização morfofuncional e molecular da transmissão intergeracional da esteatose hepática em um modelo de exposição materno fetal ao consumo excessivo de sacarose - PONTES, Jaqueline Pessoa (2024)
Adverse metabolic conditions during early life stages are linked to an increased risk of non- communicable chronic diseases, as established by the Developmental Origins of Health and Disease (DOHaD) study. Excessive sugar consumption during pregnancy by mothers negatively affects their offspring's metabolic health indicators. Metabolic Syndrome (MS), which manifests in the liver as non-alcoholic fatty liver disease (NAFLD), has been associated with increased consumption of added sugars. This study aims to investigate the metabolic mechanisms leading to the early onset of hepatic steatosis in the offspring of rats exposed to a high-sucrose diet (HSD) during the perigestational period. Female rats (Rattus novergicus) were fed either an HSD or a standard diet for 12 weeks. Diet exposure spanned pre-conception, gestation, and lactation periods. After weaning, the offspring were fed a control diet and divided into two groups: those euthanized at 30 or 90 days of life. Weight, morphological, and biochemical characteristics of the mothers (F0) and offspring were evaluated, along with molecular analyses in the offspring. The F0 HSD generation in the pregestational period showed significant differences in body weight during the perigestational period and lower liver weight compared to the CTR group, along with hypertriglyceridemia, an increase in the TyG index, and in the glucose tolerance test (GTT). Hepatic steatosis was not observed in the mothers. Regarding the offspring (males and females), the male offspring of HSD mothers showed an increase in body weight. The female offspring exposed to HSD showed significant differences in ovary and pancreas weight at 30 days compared to the CTR group. In males, at 30 days, there was a significant increase in periepididymal fat and, at 90 days, in retroperitoneal fat compared to the CTR group. Both sexes, at 30 and 90 days, developed hepatic steatosis. In females, there was an increase in hepatic triglycerides at 30 days and a greater accumulation of liver fat at 90 days, while in males, an increase in hepatic triglycerides was also observed at 90 days. Females showed greater expression of genes involved in de novo lipogenesis, such as FASN at 30 and 90 days, and PPAR-γ, PGC1α, and PPAR-α at 90 days. In contrast, males showed a reduction in PPAR-γ expression. This study revealed that perigestational exposure to a high-sucrose diet caused significant metabolic changes in the mothers and their offspring, highlighting the early onset of hepatic steatosis and changes in the expression of genes related to lipogenesis, particularly in females. Adaptive responses differed between sexes, especially in the regulation of lipogenic genes and fat accumulation in the liver. Investigating the involved signaling pathways through Western blot analysis is essential to validate and quantify the proteins associated with these genes, elucidating the molecular mechanisms of hepatic steatosis. These findings underscore the importance of preventive strategies during the perigestational period, highlighting the adverse impacts of excessive sucrose consumption on maternal metabolic health and the metabolic programming of offspring, with sex-specific implications.